TRİPTOFAN HİDROKSİLAZ GEN POLİMORFİZMİNİN İŞİTSEL OLAYA İLİŞKİN BEYİN POTANSİYELLERİNE ETKİSİ - ERGENOĞLU, Tolgay; COŞKUN, Gonca; BEYDAĞI, Hüseyin; KESKİN, Yasemin; ERDAL, Mehmet Emin; DEMİRALP, Tamer (Cerrahpaşa Medical Journal, 2019)
Background and Design.- Serotonin (5-HT) which is synthesized from tryptophan with tryptophan hydroxylase enzyme is an important neurotransmitter in the central nervous system. Tryptophan hydroxylase (TPH) is the initial step and rate-limiting enzyme in the synthesis of serotonin. Present study investigated whether A218C polymorphism on the seventh intron that is caused by adenin-cytosine transition of TPH gene has an effect on auditory event-related potentials (ERP). Forty-eight healthy male volunteers participated in this study. N100, P200 and P300 potentials elicited with auditory oddball and novelty paradigms. Subjects were grouped according to the A218C polymorphism of TPH gene identified using the PCR method. The differences in amplitude, latency and topographic distribution of ERPs between the genotype groups were tested with repeated measures ANOVA. Results.- The latency of the P200 in response to the oddball targets was longer in C/C genotype than in the A/C genotype group (p=0.007). There was also a trend for longer P200 latencies obtained with the novel stimuli of the novelty paradigm for the C/C group (p=0.079). Conclusion.- Our results suggest that differentiation in serotonergic activity that results from TPH gene polymorphism may alter auditory ERPs.